High-resolution carbon isotope chemostratigraphy of the upper Cambrian from the East Tarim Basin and implications for global correlation and paleoenvironment reconstruction - Xiao-Jun Zuo; Bo Chen; Hong-Xing Wei; Zhi-Xin Sun; Xin-Sheng Luo; Guo-Xiang Li; Zhi-Bin Huang; Miao Lu; Yong-Quan Chen; Ai-Hua Yang; Fang-Chen Zhao; Mao-Yan Zhu (Palaeoworld, 2026)

Optimization of grinding media charge Based on grinding Kinetics: A Case study of copper ore - Ruitao Liu; Qingfei Xiao; Saizhen Jin; Mengtao Wang; Xianglong Li; Yanwei Zhao; Zhong Luo; Sheng Jian; Feng Xie (Minerals Engineering, 2026)

Application and adsorption mechanism of 1-(3-(trifluoromethyl)phenyl)thiourea: A novel selective collector for flotation separation of azurite from K-feldspar - Qiuyue Sheng; Long Li; Wenjing Feng; Zhifeng Zhao; Yonghang Luo; Yuxuan Yang; Zhanglei Zhu; Ningning Zhang; Wanzhong Yin (Minerals Engineering, 2026)

Persulfate-assisted anaerobic digestion systems: advances in microbial electron transport chain reconstruction and metabolic regulation driven by reactive oxygen species - Yingjin Song; Sheng Xu; Yanshan Wang; Lan Mu; Huiling Niu; Qingyi Li; Yinjie Zhong; Yvxing Luo; Zhi Wang; Beibei Yan; Guanyi Chen (Bioresource Technology, 2026)

Phosphorus legacy advances the negative response of surface soil organic carbon to altered precipitation regimes - Qiao Liu; Fangchao Wang; Fu-Sheng Chen; Junjie Huang; Shengnan Wang; Jianjun Li; Xiangjiang Liu; Zeqing Ma; Huiming Wang; Xiaofei Hu; Yiqi Luo (Soil Biology and Biochemistry, 2026)

A comprehensive distributed hydrological framework for assessing flood responses to environmental change under multiple human disturbances - Yuhao Wang; Ke Zhang; Edwark Park; Yuning Luo; Jie Liu; Shunzhang Li; Zhaoan Zhang; Yue Kong; Sheng Wang (Journal of Hydrology, 2026)

A multiomics perspective on ecological toxicity, environmental behavior, and synthetic microbiome restoration of RDX in soil - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Yu Zhang; Xue-gang Luo (Journal of Environmental Chemical Engineering, 2026)

A physics-constrained data-driven method for predicting the damage zone extent of surrounding rock under coupled dynamic-static loading - Ce Jia; Chaojun Fan; Sheng Li; Lianpeng Dai; Mingkun Luo; Lei Yang; Haibo Li (International Journal of Rock Mechanics and Mining Sciences, 2026)

Fracture-controlled permeability evolution and methane migration pathways in abandoned coal mines: implications for abandoned mine methane recovery - Ce Jia; Chaojun Fan; Sheng Li; Mingkun Luo; Zhong Liu; Yiqi Wang; Yang Li (Fuel, 2026)

Vertically increasing rock fragment content exacerbates drought stress in Dolomite-derived soils of rocky desertification areas - Zixi Chen; Chao Luo; Sheng Li; Jia Wang; Yan Wang (CATENA, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Development of a gravity-driven self-centering rubber bearing for seismic isolation - Hong-Tai Zhang; Bing Zhao; Ping Xiang; Xue-Bin Ren; Yang Li; Li-Sheng Luo; Liang-Jiu Jia (Soil Dynamics and Earthquake Engineering, 2026)

Ecotoxicological impacts of TNT and its key transformation intermediates in freshwater microcosms and their effective remediation by a bicarbonate-activated peroxide system - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo; Yong-bing Zhu; San-ping Zhao (Journal of Water Process Engineering, 2026)

A synthetic microbiome drives a multi-omics response to remediate 1,4-dithiane–contaminated soil and simultaneously suppresses antibiotic resistance genes - Xu Yang; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Journal of Hazardous Materials, 2026)

Impact of different animal and plant proteins on the structure, rheology and texture of nanocellulose composite oleogels - Yubo Zhu; Bing Zhao; Ai Li; Jia Luo; Jienan Li; Jun Sheng; Yang Tian; Xiufen Li (Food Hydrocolloids, 2026)

Seasonal source shifts and toxicity implications of PM2.5-bound polycyclic aromatic hydrocarbons in central China: The critical role of underrated local emissions - Runqi Zhang; Sheng Li; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Pollution Research, 2026)

Effects of Poly-γ-Glutamic Acid Application on Greenhouse Gas Emissions and GrainYield Under Different Direct-Seeding Methods in Paddy Rice - Rong Huang; Shi-hao Li; Hong-yan Li; Qian Luo; Yu-quan Fu; Qu-chen Zhou; Xiang-yu Huang; Xue-zhu Du; Feng Sheng (Journal of Soil Science and Plant Nutrition, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

Nitric acid-modified co-pyrolyzed biochar from gentamicin mycelial residue and biomass regulates cattle manure composting: Reducing carbon loss and enhancing humification - Yingjin Song; Huiling Niu; Yamei Zeng; Guanyi Chen; Zeng Dan; Beibei Yan; Lan Mu; Yuxing Luo; Yinjie Zhong; Sheng Xu; Qingyi Li; Anna Jin (Journal of Environmental Management, 2026)

Walnut oil oleogel constructed by cellulose nanofiber and walnut protein isolate: Structure, rheology characterization and complementary stabilization effect - Yubo Zhu; Bing Zhao; Jia Luo; Jienan Li; Jun Sheng; Yang Tian; Xiufen Li (Food Chemistry, 2026)

Elucidating functional group governance for catalytic synthesis of bio-based aromatic amines - Ge-liang Xie; Yu Luo; Kai-cheng Xia; Sheng-ren Li; Lujiang Xu; Zhen Fang (Biomass and Bioenergy, 2026)

Tacrolimus combined with everolimus versus sirolimus in organ transplantation: a comparative pharmacovigilance analysis of the FDA Adverse Event Reporting System - Yanlang He; Chen Luo; Shuangyan He; Sha Li; Haolin Zhou; Sheng Wei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Trophic plasticity drives species-specific adaptive responses to seasonal variability in reef-building corals - Xiao-Lei Yu; Lei Jiang; Yong Luo; Lin-Tao Huang; Peng Zhang; Zhan-Wei Li; Cheng-Yue Liu; Pan Zhang; Jian-Yu Chen; Sheng Liu; Gui-Xin Dong; Hui Huang (Coral Reefs, 2026)

Molecularly integrated dynamic chitosan network with topology-adaptive glucose/ROS responsiveness for coupled drug release and immunoregulation - Yuxiang Li; Sheng Dong; Ran Yu; Runjie Liu; Hengxi Xu; Hainuo Li; Wenbo Ming; Guochao Liao; Rong Zhang; Zhongqiu Liu; Wenxian Wang; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

DNA-based one-pot rapid biosensing platform integrating turn-back loop primer-accelerated LAMP and Pyrococcus furiosus Argonaute for meat visual authentication - Sheng Ding; Jing Li; Minglong Yang; Yujia Song; Xiangke Niu; Mei Li; Yao Luo (Journal of Zhejiang University-SCIENCE B, 2026)

Surface wave tomography reveals potential ice-bedrock interaction in the Larsemann Hills, East Antarctica - Changcheng Li; Lei Fu; Zhengbo Li; Kun Luo; Sheng Dong; Hengxin Ren; Xiaofei Chen (Science China Earth Sciences, 2026)

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

Geochemistry and Li isotopes of micas: implications for granitic magma evolution and fluid exsolution at the Laiziling Sn-polymetallic deposit in southern Hunan Province (South China) - Kaixuan Li; Sheng Huang; Cheng-Biao Leng; Ruyi Zhao; Dazhao Wang; Xianping Luo (Mineralium Deposita, 2026)

High-resolution electrical resistivity imaging of crust beneath Helishan mountains in Hexi Corridor, implications for basin-range coupling and hydrocarbon generation mechanism - Xian-zhong Luo; Sheng Xia; Jun-lu Wang; Yao-tian Yin; Hui Chen; Zhan Liang; Long-long Li (Applied Geophysics, 2026)

Nutrient input of coastal aquaculture may affect growth of mangrove following intermediate disturbance hypothesis: critical thresholds and spatial relationship coupling - Haonan Li; Haitao Chen; Longtian Huang; Chunxiang Liu; Jin Luo; Haoyu Wang; Mengji Zhang; Xiuqiong Liang; Yongze Xing; Wenlu Lan; Xiaoyan Peng; Sheng Fang; et al. (Marine Pollution Bulletin, 2026)

Plant bioavailable phosphorus content in animal manure- and sewage sludge-based char and ash: Effect of thermal treatment temperature and condition - Xuan Luo; Wei Ding; Adi Radian; Ling Tan; Yukun Sheng; Cheng Li; Zhenyu Wu; Keke Xiao (Waste Management, 2026)

Population Genomics of a Cosmopolitan Weed Provides Insights Into Its Local Adaptation and Recent Demographic History - Marilia Souza Lucas; Christoph Rosche; Isabell Hensen; Stefan G. Michalski; Dávid U. Nagy; Diana Gamba; Renske E. Onstein; Karime Abidkulova; Mohammad Al‐Gharaibeh; Ali A. Al‐Namazi; Sirwan Babaei; Fernando Bastida; et al. (Molecular Ecology, 2026)
Invasive plant species present a growing ecological and economic challenge, and often adapt rapidly to their novel environments through complex demographic and evolutionary processes. Invasion genomics offers powerful tools to disentangle these processes, but most studies rely on geographically narrow sampling across native and non‐native ranges. Erigeron canadensis is a cosmopolitan weed native to North America that has successfully invaded diverse climates worldwide. We used double‐digest restriction site‐associated DNA sequencing (ddRADseq) to investigate the genetic diversity and structure of 280 E. canadensis populations across the Northern Hemisphere. We found that native and non‐native populations maintained comparable genetic diversity. Population structure analyses revealed four genetic clusters that were mainly differentiated along latitudinal and aridity gradients. However, one cluster was strongly overrepresented in the non‐native compared to the native range. In the native range, genetic differentiation was shaped by spatial and environmental gradients, while in non‐native regions human‐mediated dispersal and repeated introductions disrupted environmentally driven genetic structure. Migration network analyses revealed limited intercontinental connectivity and a possible role of long‐distance dispersal in within‐range expansions. Genomic offset analyses showed that genotype‐environment mismatches in non‐native populations associated with reduced growth and reproduction. Together, our results indicate that the invasion dynamics of E. canadensis were driven by multiple introductions, population admixture, and lineage sorting, while some genotypes contributed disproportionately to the spread of this invader. The presence of apparent maladaptation suggests that even long‐established invaders may still be evolving in response to their novel environment, raising concerns about potential future expansions.

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Field observations reveal biomass burning and cooking as the significant sources of PM2.5-bound organic acids in Central China - Ziyue Xiang; Runqi Zhang; Sheng Li; Bin Xu; Qiongwei Zhang; Jun Wang; Datong Luo; Zhan Liu; Xinming Wang (Atmospheric Environment, 2026)

Flavonoid components, antibacterial and anti‑inflammatory activities of extracts from different organs of Sapindus mukorossi Gaertn - Wenjiao Li; Guohua Zhang; Danyi Wu; Qiwei Xuan; Zhuyan Zhang; Yuancheng Luo; Xiangyu Zhu; Weiyi Qin; Fujin Liu; Zhaojun Sheng (Natural Product Research, 2026)

Study and application of energy-dissipating yielding support for large deformation in hard rock tunnel subjected to extremely high geostress - Sheng Pi; Mingnian Wang; Xun Luo; Li Yu; Youlin Qin (Tunnelling and Underground Space Technology, 2026)

Synergistic regulation of calcium hydroxide and ARC microbial inoculant on rhizosphere microbiota and soil chemical properties during peanut middle growth stages in acidic red soils - Gongming Wu; Hong Yu; Ningbo Zeng; Zinan Luo; Sheng Gao; Qi Liang; Lin Li; Peiwu Li; Zemao Yang; Dengwang Liu (Rhizosphere, 2026)

Drying methods impact bioactive compounds in Siraitia grosvenorii fruit: Metabolomic insights - Li Li; Lihong Xie; Ping Yi; Ting Gan; Zhenmei Fan; Min Huang; Shiqi Wang; Dan Luo; Rui Pang; Fenglai Lu; Jinfeng Sheng; Jian Sun; et al. (Food Chemistry, 2026)

Dietary carbohydrate fuels a metabolic strategy for osmotic adaptation, enhancing growth and resilience of Litopenaeus vannamei in low-salinity water - Zhao Li; Zhi Luo; Sheng-Wei Lin; Feng-Lu Han; Chang Xu; Er-Chao Li (Aquaculture International, 2026)

Multiomics approaches identify immunometabolic crosstalk in triploid cyprinid fish after Edwardsiella tarda 1 l-4 infection - Ruo-Xing Yu; Ting Luo; Qin-Yang He; Zi-Rou Zhong; Jie Peng; Yao-Hui Li; Zhuang-Wen Mao; Ming-Zhu Huang; Zi-Le Qin; Xu-Ying Kuang; Zi-Xuan Fang; Jian Li; et al. (Aquaculture, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

A concept-drift-driven hybrid modeling framework for high-resolution ambient surface NO2 retrieval in Beijing-Tianjin-Hebei Region, China - Junyu Wang; Jian Qian; Jiayi Chen; Caiying Luo; Sheng Li; Na Yang; Ruoyu Li; You Zou; Tao Zhang; Fei Yin; Chenglin Tao; Nan Wang; et al. (Journal of Hazardous Materials, 2026)

Dispersible reduced graphene oxide enhances the biodegradation of sulfamethoxazole by white rot fungus Phanerochaete chrysosporium - Yunxuan Hu; Juncheng Li; Xiting Wang; Lejie Pan; Lu Jiang; Lei Luo; Shizhe Peng; Yue Yuan; Qinmin Zhong; Xian Wu; Wei Li; Yubing Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Synergistic effects of DHA and choline delivered via co-encapsulated microcapsules in infant formula Rice cereal: Enhanced cognitive function and molecular mechanisms in mice - Xinyao Liu; Zuohua Xie; Yuqing Zhang; Meng Wei; Xinggang Ni; Zhang Siqiong; Lu Ling; Sheng Wengsheng; Ting Luo; Jing Li (Food Research International, 2026)

Arsenic exposure reduces testosterone synthesis partially by evoking Leydig cell ferroptosis in mouse testes - Xiao-Yi Zhang; Yan Luo; Nan-Nan Liang; Qiang-Sheng Li; Zhi-Hui Zhang; Yi-Chao Huang; De-Xiang Xu (Environmental Pollution, 2026)

Integrated Transcriptomic and Metabolomic Analyses Reveal Molecular Mechanism in Hybrid Crucian Carp (Carassius cuvieri♀ × Carassius auratus Red var♂) after Gut Infection with Aeromonas hydrophila L3-3 - Fei Wang; Wei-Sheng Luo; Zi-Le Qin; Jian Li; Si-Ze Xiao; Sheng-Wei Luo (Marine Biotechnology, 2026)

First report of papaya leaf curl China virus infecting Phaseolus vulgaris in China - Chenchen Jing; Lu Luo; Ke Li; Sheng Li; Yeting Zhao; Xue Feng (Journal of Plant Diseases and Protection, 2026)

Microalgae as a Synergistic Enhancer for In Situ and Ex Situ Treatment Technologies in Sustainable Shrimp Aquaculture: A Critical Review - Sheng Dong; Fei Huang; Xianghui Zou; Qiulan Luo; Jiancheng Li (Fishes, 2026)
The intensification of shrimp aquaculture is crucial for global food security, but poses significant environmental challenges. This review critically assesses the strengths and bottlenecks of two main treatment paradigms: in situ systems, chiefly biofloc technology (BFT), and advanced ex situ systems, such as recirculating aquaculture systems (RASs), constructed wetlands (CWs), and membrane bioreactors (MBRs). Although BFT enables nutrient recycling, it suffers from nitrate accumulation and a high energy demand. Likewise, ex situ technologies can achieve a high treatment efficiency, but contend with high costs, large footprints, or membrane fouling. In this review, we propose the strategic integration of microalgae, representing a universal and synergistic solution for overcoming these disparate bottlenecks. We dissect how a microalgal co-culture can simultaneously remove nitrate and reduce the aeration costs in BFT systems. Furthermore, we explore how microalgae-based units can serve as efficient polishing steps for RASs, enhance the performance of CWs, and mitigate fouling in MBRs. This review delves into the fundamental mechanisms of the microalgal–bacterial symbiosis that underpins these enhancements. Finally, we highlight the valorization of the resulting algal biomass as a high-value aquafeed ingredient, which can transform waste management into a value-creation opportunity. This review aims to provide a comprehensive roadmap for developing next-generation, microalgae-enhanced aquaculture systems.

Layer-by-layer assembly pesticide carrier with the balance between adhesion and controlled release for pest control - Yafei Jiang; Ying He; Xiaohui Su; Lijuan Luo; Hedong Bian; Guohuan Huang; Sheng Li (Journal of Cleaner Production, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

GHydroMod-SIM-DAI v1.0: A new distributed hydrological model capable of dynamically recognizing runoff generation mechanisms and accounting for aboveground and underground anthropogenic impacts - Yuhao Wang; Ke Zhang; Yuning Luo; Qinuo Zhang; Zhijia Li; Cheng Yao; Xinyu Chen; Sheng Wang; Jie Liu; Chuntang Zhang; Shunzhang Li (Journal of Hydrology, 2025)

An abnormal Taylor cap observed on the west side of the Beipo seamount in the South China Sea - Zhengpu Luo; Dezhou Yang; Wuhong Guo; Lingjing Xu; Yuxuan Li; Xiquan Liu; Sheng Dai; Baoshu Yin; Kuidong Xu (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Identification of writers and erasers in tomato and their response to drought stress and hormones - Yushi Lu; Sheng Luo; Jing Cui; Yuxia Yao; Yuna Pan; Wenjin Yu; Changxia Li (Plant Cell Reports, 2025)

Hippocampal Extracellular Matrix Protein Laminin β1 Regulates Neuropathic Pain and Pain-Related Cognitive Impairment - Ying-Chun Li; Pei-Yang Liu; Hai-Tao Li; Shuai Wang; Yun-Xin Shi; Zhen-Zhen Li; Wen-Guang Chu; Xia Li; Wan-Neng Liu; Xing-Xing Zheng; Fei Wang; Wen-Juan Han; et al. (Neuroscience Bulletin, 2025)

mecoturn: An R package for deciphering microbial turnover patterns along gradients - Chi Liu; Jiahui Luo; Chunmiao Lu; Tianlong Sheng; Raymond Jianxiong Zeng; Xiangzhen Li; Minjie Yao (Soil Ecology Letters, 2025)

Domain Adaptation with Deep Feature Clustering for Pseudo-Label Denoising in Heterogeneous SAR Image Classification - Sheng-Jie Luo; Zhi-Gang Liu; Xi-Hai Li; Yi-Ting Wang; Xiao-Niu Zeng; Zhi-Hao Zheng; Heng Li (Applied Geophysics, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Bifunctional metal-organic framework Nanozymes with flexibly tunable valence states for dual-mode detection of organophosphorus pesticides - Mai Luo; Yao Peng; Jihai Cai; Tiantian Jiang; Sheng Gong; Shiyao Hua; Ting Wang; Sijia Wu; Shuangpeng Wang; Jinchao Wei; Peng Li (Food Chemistry, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

Source reconstruction for atmospheric radionuclide leakage: Recent advances in decoding information from atmospheric transport physics - Yuhan Xu; Xinpeng Li; Haoyuan Luo; Wei Wang; Sheng Fang (Journal of Hazardous Materials, 2025)

The impact of cropland displacement on crop production greenhouse gas emissions: Evidence from China - Siyu Sheng; Feixue Li; Bohan Yang; Tingyu Luo (Journal of Environmental Management, 2025)

Experimental and mechanistic study on the removal of elemental mercury in coal-fired flue gas by SO2-modified activated coke within a wide temperature range - Lingxuan Chen; Guangqian Luo; Mingyu Yu; Chunhui Sun; Yi Xiao; Yongda Huang; Sheng Chen; Ping Xiao; Shiqing Wang; Xian Li; Hong Yao (Fuel, 2025)

Identifying gelatin source by mass spectrometry: A review - Xiao-Mei Sha; Le-Ying Yang; Hui Wang; Jie Cheng; Hao-Sheng Luo; Li-Jun Zhang; Zi-Zi Hu; Zong-Cai Tu (Food Chemistry, 2025)

Genome-wide DNA methylation and transcriptome analysis of the Pacific white shrimp Penaeus vannamei post-WSSV infection - Xupeng Li; Jingjing Wang; Sheng Luan; Kun Luo; Jie Kong; Xianhong Meng (Fish & Shellfish Immunology, 2025)

Superwetting aqueous electrolyte for highly stable zinc anodes - Yurou Wu; Huijian Wang; Meilan Xie; Kai Fu; Zhendong Li; Xingyuan Dai; Jiarui Zhang; Lihan Wang; Xiaoshu He; Yidan Luo; Sheng Ouyang; Wen He; et al. (Chemical Engineering Journal, 2025)

Transcriptome Reveals Molecular Characteristics and Immune Response in Triploid Cyprinid Fish Infected with a Novel Pathogenic Aeromonas sp. AS1-4 - Qin-Yang He; Jie Peng; Ruo-Xing Yu; Ting Luo; Yao-Hui Li; Zi-Rou Zhong; Zi-Le Qin; Fei Wang; Jian Li; Sheng-Wei Luo (Marine Biotechnology, 2025)

Hyperoside extends lifespan in Caenorhabditis elegans through SEK-1/PMK-1/SKN-1 pathway - Xin-Tian Yu; Lin Shi; Qiong Huang; Bao Li; Yan-Qing Li; Li-Lan Ou; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2025)

Towards targeted heat resilience: A conceptual framework of urban heat-proof in Chengdu, China - Yutong Li; Sining Zhang; Xiaopeng Li; Shixian Luo; Qingling Liu; Yanping Zhong; Sheng Liu (Sustainable Cities and Society, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Diazotrophic communities shift with organic fertilizer substitution and growth stages in tomato field soil - Chunmiao Lu; Jiahui Luo; Tianlong Sheng; Yuebin Xie; Yuchen Xian; Yanqiong Jiang; Xiangzhen Li; Minjie Yao (European Journal of Soil Biology, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Assessing the stock recovery of Coilia nasus in the Yangtze River-Poyang Lake waterway and adjacent waters, using the length-based Bayesian biomass method - Yulan Luo; Qun Xu; Sheng Wang; Zhengli Luo; Chiping Kong; Legen Peng; Bao Zhang; Baolong Bao; Lekang Li; Xiaoling Gong (Frontiers in Marine Science, 2025)
The comprehensive ten-year fishing ban implemented in the Yangtze River on January 1, 2021, represents a critical ecological conservation measure and national strategic priority in China. Assessment of the ban’s effectiveness is essential to guide future long-term conservation efforts. This study systematically analyzed changes in the stock structure and biomass dynamics of Coilia nasus in the Yangtze River-Poyang Lake waterway and adjacent waters from 2019 to 2024 using the Length-Based Bayesian Biomass (LBB) method. Results showed a notable improvement in age structure, with the proportion of four-year-old individuals increasing from 3.2% in 2020 to 17.2% in 2024, effectively reversing the previous trend toward younger, smaller fish. The average body length and weight increased significantly, from 271.20 ± 38.44 mm, 68.52 ± 33.26 g in 2019 to 305.53 ± 37.99 mm, 88.02 ± 32.01 g in 2024 ( P < 0.05). The dominant size classes shifted step by step, from 250 – 260 mm, 50 – 60 g in 2019 to 330 – 340 mm, 120 – 130 g in 2024. According to the LBB model, the relative biomass ( B/B 0 ) increased from 0.17 to 0.68, and biomass relative to the maximum sustainable yield ( B/Bmsy ) rose from 0.48 to 1.9, demonstrating a transition in the stock status from “outside of safe biological limits” to “healthy” from 2019 to 2024. These trends, along with increases in the Lmean/Lopt , Lc/Lcopt ratios and other indexes, highlight improvements in size structure and a greater presence of larger individuals. In addition, the fishing mortality to natural mortality ratio ( F/M ) markedly declined from 2.6 in 2019 to 0.37 in 2024, underscoring the substantial alleviation of fishing pressure under the ban. To further validate these findings, SPR was estimated using the LBSPR model, increasing from 0.19 to 0.42 and suggesting improved reproductive sustainability. These findings provide strong evidence that the fishing ban has played a critical role in the stock recovery of C. nasus and mitigating the effects of overfishing.

Genomic selection for hard-to-measure traits in aquaculture: Challenges in balancing genetic gain and diversity - Ziyi Kang; Jie Kong; Qi Li; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Zhaoxin Wang; et al. (Aquaculture, 2025)

Molecularly engineered visible-light-driven dithienylethenes: near quantitative photocyclization yield, polymorphic control and reconfigurable 3D-printed devices - Qing Yan; Jiaxian Lu; Zhifeng Ma; Miao Luo; Chengpeng Li; Sheng Wang; Jun Ren (Chemical Engineering Journal, 2025)

Recommendations of Stable Mg, Si, V, Fe, Cu, Zn, Rb, Sr, Ag, Cd, Ba, and U Isotope Compositions for Multiple Geological References - Jinting Kang; Xuqi Chen; Xi Deng; Yuan Fang; Haichuan Jiang; Chengyihong Liu; Cuihua Luo; Xing Li; Yuchao Lin; Zhaoqi Ren; Jiaru Sheng; Xue Tang; et al. (Journal of Earth Science, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

Screening novel anti-inflammatory peptides inhibiting the NLRP3 inflammasome from UHPLC-MS/MS-characterized peptide profiles of cocoa tea protein hydrolysates - Hai-Biao Gong; Chang-Yu Yan; Hui-Er Ye; Shuo-Yan Tan; Shi-Sheng Chen; Jian-Wen Ye; Wan-Yang Sun; Hong-Li Tan; Xiang Luo; Jie Niu; Kun Li; Jing-Hao Wang; et al. (Food Research International, 2025)

Thinning and tending could enhance the understory regeneration potential of seed bank during the subtropical pine forest restoration - Chao Luo; Sheng Li; Jiejie Jiao; Jia Wang; Zixi Chen; Yufei Zhou (Forest Ecology and Management, 2025)

The Guanylate Cyclase Soluble Subunit Alpha-1 Deficiency Impairs Angiogenesis in Zebrafishes and Mice: In Vivo and In Vitro Studies - Man Luo; Dongcan Mo; Jianli Li; LiuYu Liu; Xiaoling Li; Jing Lin; Jie Liang; Fei Ye; Xiaozuo Lin; Pingkai Wang; Xiaoju Wu; Yinan Zeng; et al. (Molecular Neurobiology, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Ultra-low temperature removal of element mercury in coal-fired flue gas by activated carbon - Renjie Zou; Tong Sun; Guangqian Luo; Lingxuan Chen; Li Wang; Sheng Chen; Shiqing Wang; Xian Li; Ping Xiao; Hong Yao (Fuel, 2025)

Spatial retention, absorption, transport, and enrichment of microplastics in mangrove sediment complex system - Xiuqiong Liang; Chunxiang Liu; Haoyu Wang; Haonan Li; Jin Luo; Gang Luo; Wei Hu; Wenlu Lan; Leishi Wu; Sheng Fang; Yan Tian; Xiang Sun (Environmental Pollution, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Hypoglycemic effect of dietary fibers from Moringa oleifera leaves: In vitro and in vivo studies - Xiufen Li; Jinye Yong; Bing Zhao; Yubo Zhu; Jia Luo; Jun Sheng; Yang Tian (Food Research International, 2025)

Designed amino acid-based deep eutectic solvents as a platform to functionalize biomedical elastomers by polyaddition reactions - Ao Zhen; Ao Wang; Xirui Long; Xiao Wang; Nan Sheng; Qing Tang; Jiehua Li; Hong Tan; Feng Luo; Zhen Li (Chemical Engineering Journal, 2025)

Antibacterial antioxidant polyurethane/curcumin patch with anti-swelling ability for tissue adhesion and treatment of oral ulcers - Xiaolei Guo; Lin Yang; Nan Sheng; Xirui Long; Zhen Li; Feng Luo; Jiehua Li; Hong Tan (Chemical Engineering Journal, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Genomic selection of resistance to acute hepatopancreatic necrosis disease in Litopenaeus vannamei - Mianyu Liu; Xupeng Li; Jie Kong; Xianhong Meng; Kun Luo; Juan Sui; Ping Dai; Jian Tan; Jiawang Cao; Baolong Chen; Hongjie Wang; Sheng Luan (Aquaculture, 2025)

Comparative Analysis of the Probiotic Features of Lysinibacillus and Enterobacter Strains Isolated from Gut Tract of Triploid Cyprinid Fish - Zi-Xuan Fang; Xu-Ying Kuang; Yao-Hui Li; Ruo-Xing Yu; Fei Wang; Sheng-Wei Luo (Current Microbiology, 2025)

Immunosuppressive leucosceptrane-type sesterterpenoids with antipodal cyclopentenones isolated from Leucosceptrum canum - Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Ting-Ting Zhou; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

7-Hydroxycoumarin and its conjugated metabolites interact with organic anion transporters 1 and 3 in vitro and in vivo - Lijun Luo; Yongchun Chang; Weilin Zhang; Xiao Liu; Junpu Ge; Jieyi Chen; Yan Li; Dan Zhang; Li Sheng (Chemico-Biological Interactions, 2025)

17α-methyltestosterone induced hepatocyte apoptosis through endoplasmic reticulum stress in Takifugu fasciatus - Xuanyin Chen; Sheng Luo; Yanfang Li; Rui Li; Xiaojun Li; Zhengyang Hu; Shaowu Yin; Tao Wang (Journal of Oceanology and Limnology, 2025)

Whole-genome mutagenesis of whiteleg shrimp (Litopenaeus vannamei) by ARTP and analysis of its mutational characteristics - Qiang Fu; Jingxin Zhou; Sheng Luan; Kun Luo; Baolong Chen; Jiawang Cao; Xupeng Li; Qun Xing; Jie Kong; Xianhong Meng (Aquaculture, 2024)

PhytOC sequestration characteristics and phytolith carbon sink capacity of the karst grasslands in southwest China - Mengxia Luo; Linjiao Wang; Li Liu; Lukang Song; Xiaxia Lu; Maoyin Sheng (Science of The Total Environment, 2024)

Hydrogen sulfide alleviates cadmium stress in germinating carrot seeds by promoting the accumulation of proline - Miao Sun; Huan-Xuan Qiao; Tao Yang; Peng Zhao; Jun-Hao Zhao; Jia-Ming Luo; Hai-Ye Luan; Xiang Li; Sheng-Cai Wu; Ai-Sheng Xiong (Journal of Plant Physiology, 2024)

iRainSnowHydro v1.0: A distributed integrated rainfall-runoff and snowmelt-runoff simulation model for alpine watersheds - Yuning Luo; Ke Zhang; Yuhao Wang; Sheng Wang; Nan Wu; Shunzhang Li; Qinuo Zhang; Xinyu Chen; Hongjun Bao (Journal of Hydrology, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

Mitigation effects of exogenous acetic acid on drought stress in Cunninghamia lanceolata - Menghan Li; Shuang Gao; Jianxun Luo; Zeyu Cai; Sheng Zhang (Plant and Soil, 2024)

Comparative analyses of immune gene profiles and antioxidant capabilities in the midgut and liver of three species of grass carps (Ctenopharyngodon idella) following gut infection with Aeromonas hydrophila - Wei-Sheng Luo; Zi-Han Xu; Qin-Yang He; Jie Peng; Fei Wang; Jian Li; Sheng-Wei Luo (Aquaculture International, 2024)

An efficient flavonoid glycosyltransferase NjUGT73B1 from Nardostachys jatamansi of alpine Himalayas discovered by structure-based protein clustering - Mingkang Feng; Yuan Liu; Bin He; Hairong Zhong; Axiang Qu-Bie; Min Li; Mengting Luo; Xiaoming Bao; Ying Li; Xinjia Yan; Huachun Sheng; Zhifeng Zhang; et al. (Phytochemistry, 2024)

Ganospirones A−G, seven undescribed spiro-meroterpenoids from Ganoderma lucidum and their biological activities - Dan Li; Sheng-Hong Li; Qiang Gao; Qi Luo; Yong-Xian Cheng (Phytochemistry, 2024)

Reversible behavior of photochromic process controlled by dielectric microenvironment - Miao Luo; Juan Zhao; Qing Yan; Chengpeng Li; Yanyan Liu; Zhan Yang; Zhu Mao; Sheng Wang; Zhenguo Chi (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Simulation and experimental study of gas-phase diffusion coefficient of selenium dioxide - Xiaolong Wu; Renjie Zou; Guangqian Luo; Li Wang; Can Fang; Sheng Chen; Xian Li; Hong Yao (Science of The Total Environment, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Use of Tirofiban to Prevent Ischemic Events in Patients with CYP2C19 Loss-of-Function Alleles during Flow Diversion of Intracranial Aneurysm: A Multicenter Cohort Study - Yangyang Zhou; Huibin Kang; Wenqiang Li; Bin Luo; Chao Wang; Ruhang Xie; Yongnan Zhu; Qichen Peng; Yisen Zhang; Jian Liu; Ying Zhang; Shiqing Mu; et al. (Translational Stroke Research, 2024)

Microbial metabolism strengths carbon sequestration and crop yield in upland red soil after long-term ex situ incorporation of straw - Li Tang; Xiaobin Guo; Daoyou Huang; Xiaomeng Wei; Hao Sheng; Pei Luo; Ping Zhou; Wei Gao; Yan Li; Miaomiao Zhang; Wei Zheng; Jinshui Wu (Journal of Soils and Sediments, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Selenium nanoparticles alleviates cadmium induced hepatotoxicity by inhibiting ferroptosis and oxidative stress in vivo and in vitro - Chunyan Shao; Tongwang Luo; Shujie Wang; Zhuoyue Li; Xiaoqiang Yu; Ya Wu; Sheng Jiang; Bin Zhou; Quanjiang Song; Shengzhe Song; Xiaodu Wang; Houhui Song (Chemosphere, 2024)

Theoretical analysis of naproxen reaction with sulfate and hydroxyl radicals in the aqueous phase: Investigating reactive sites and reaction kinetics - Ji-Feng Yang; Wan-Li You; Deng You; Li-Ying Zheng; Jun-Ling Jin; Sheng-Lian Luo (Chemosphere, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Enhancement of selenium removal in coal-fired flue gas across wet flue gas desulfurization spray tower by internal components-part 1: Demister and wall ring - Renjie Zou; Zehua Li; Guangqian Luo; Haoyu Zhang; Can Fang; Li Wang; Min Lyu; Yongda Huang; Sheng Chen; Xian Li; Hong Yao (Journal of Cleaner Production, 2024)

Effects of cellulose diameter on the formation and rheological properties of edible walnut oleogels structured by cellulose nanofiber - Yuxuan Zou; Yang Tian; Bing Zhao; Jienan Li; Jia Luo; Jun Sheng; Xiufen Li (Food Hydrocolloids, 2024)

Structure, rheology and stability of walnut oleogels structured by cellulose nanofiber of different lengths - Xiufen Li; Bing Zhao; Yuxuan Zou; Guanshui Guo; Jienan Li; Jun Sheng; Yang Tian; Jia Luo (Food Hydrocolloids, 2024)

Recent advances in hydrogen process safety: Deflagration behaviors and explosion mitigation strategies - Peng Yang; Tao Wang; Yuhuai Sheng; Yingying Yu; Ruikang Li; Bin Su; Fangming Cheng; Jiao Qu; Jun Deng; Zhenmin Luo (Process Safety and Environmental Protection, 2024)

Leaf area index estimation in maize and soybean using UAV LiDAR data - Shezhou Luo; Weiwei Liu; Qian Ren; Hanquan Wei; Cheng Wang; Xiaohuan Xi; Sheng Nie; Dong Li; Dan Ma; Guoqing Zhou (Precision Agriculture, 2024)

CCL2 Potentiates Inflammation Pain and Related Anxiety-Like Behavior Through NMDA Signaling in Anterior Cingulate Cortex - Huan Guo; Wen-chao Hu; Hang Xian; Yun-xin Shi; Yuan-ying Liu; Sui-bin Ma; Kun-qing Pan; Sheng-xi Wu; Li-yan Xu; Ceng Luo; Rou-gang Xie (Molecular Neurobiology, 2024)

Multiomics Analyses Explore the Immunometabolic Interplay in the Liver of White Crucian Carp (Carassius cuvieri) After Aeromonas veronii Challenge - Fei Wang; Zi-Rou Zhong; Qing Xie; Jie Ou; Ning-Xia Xiong; Ming-Zhu Huang; Shi-Yun Li; Gang Hu; Zi-Le Qin; Sheng-Wei Luo (Marine Biotechnology, 2024)

Astaxanthin Rescues Memory Impairments in Rats with Vascular Dementia by Protecting Against Neuronal Death in the Hippocampus - Na Wei; Luo-man Zhang; Jing-Jing Xu; Sheng-lei Li; Rui Xue; Sheng-li Ma; Cai Li; Miao-miao Sun; Kui-sheng Chen (NeuroMolecular Medicine, 2024)

Learning-based double layer control method of yaw stability simulation research for rear wheel independent drive electric tractor plowing operation - Zhen-hao Luo; Bin Xie; Zhong-ju Chen; Sheng-li Zhang; Zi-hao Zhao; Bo-wen Zheng; Chang-kai Wen; Zheng-he Song (Computers and Electronics in Agriculture, 2024)

Oxymatrine induces apoptosis in non-small cell lung cancer cells by downregulating TRIM46 - Yi Zhong; Biaobiao Luo; Min Hong; Sheng Hu; Dian Zou; Yang Yang; Shaozhong Wei; Mohammad Omar Faruque; Shuang Dong; Xianmin Zhu; Xiaoyu Li; Yuanxiang Li; et al. (Toxicon, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Tumor necrosis factor α1 decreases mucosal immune and antioxidant response in the midgut of hybrid fish (white crucian carp ♀ × red crucian carp ♂) - Ke‐Xin Li; Ning‐Xia Xiong; Jin‐Fang Huang; Shi‐Yun Li; Jie Ou; Fei Wang; Sheng‐Wei Luo (Journal of Fish Biology, 2024)
Tumor necrosis factor α1 (TNFα) is a pleiotropic cytokine involved in immune regulation and cellular homeostasis, but the crucial role of TNFα in fish gut remained unclear. The current study aimed to evaluate the immunoregulatory function of TNFα1 on gut barrier in a novel hybrid fish (WR), which was produced by crossing white crucian carp ( Carassius cuvieri , ♀) with red crucian carp ( Carassius auratus red var, ♂). In this study, WR ‐tnfα1 sequence was identified, and a high‐level expression was detected in the intestine. Elevated levels of WR ‐tnfα1 expressions were detected in immune‐related tissues and cultured fish cells on stimulation. The appearance of vacuolization and submucosal rupture was observed in TNFα1‐treated midgut of WR, along with elevated levels of goblet cell atrophy, whereas no significant changes were detected in most expressions of tight‐junction genes and mucin genes. In contrast, WR receiving gut perfusion with WR‐TNFα1 showed a remarkable decrease in antioxidant status in midgut, whereas the expression levels of apoptotic genes and redox responsive genes increased sharply. These results suggested that TNFα1 could exhibit a detrimental effect on antioxidant defense and immune regulation in the midgut of WR.

Research on seedling sowing method based on high voltage electrostatic characteristics - Sheng Sun; Bin Hu; Jinhu Ma; Xin Luo; Mengyu Guo; Junwei Li; Luochuan Xu; Xiaoyun Xu (Computers and Electronics in Agriculture, 2024)

Optimal open nucleus breeding system for long-term genetic gain in the Pacific white shrimp using genomic selection - Ziyi Kang; Jie Kong; Juan Sui; Ping Dai; Kun Luo; Xianhong Meng; Junyu Liu; Baolong Chen; Jiawang Cao; Jian Tan; Qiang Fu; Qi Li; et al. (Aquaculture, 2024)

Significant differences in usage of antibiotics in three Chinese cities measured by wastewater-based epidemiology - Xiaozhe Luo; Sheng Han; Yue Wang; Peng Du; Xiqing Li; Phong K. Thai (Water Research, 2024)

Ultra-high electron affinity and peripheral electronegativity co-constructing all-organic dielectrics with outstanding capacitive performance at high temperature - Xiaona Li; Hang Luo; Yuting Wan; Bo Peng; Yuan Liu; Sheng Chen; Dou Zhang (Chemical Engineering Journal, 2024)

The alternation of flood and ebb tide induced arsenic release and migration from coastal tidal flat sediments in Yellow Sea wetlands: An ex-situ study - Ting Luo; Yan Sun; Weihao Liang; Qining Zheng; Sheng Kong; Lili Xue; Li Yan (Journal of Cleaner Production, 2024)

Metal element-based adsorbents for phosphorus capture: Chaperone effect, performance and mechanism - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Chemosphere, 2024)

Electrochemical performance enhanced by solvent infiltration strategy to increase micro-mesopores within wood tracheid walls - Jie Ouyang; Liangliang Zhou; Yi Tian; Wanning Xiong; Lixin Wang; Xi Ren; Qingquan Sheng; Zejun Li; Xiubo Liu; Yongfeng Luo (Journal of Cleaner Production, 2024)

Unusual weakening trend of the East Asian winter monsoon during MIS 8 revealed by Chinese loess deposits and its implications for ice age dynamics - Qingzhen Hao; Shuzhen Peng; Xinbo Gao; Slobodan B. Marković; Sheng-Hua Li; Junjie Zhang; Fengjiang Li; Long Han; Yu Fu; Xuechao Wu; Luo Wang; Bing Xu; et al. (Global and Planetary Change, 2024)

Formation mechanism of a disaster chain in Loess Plateau: A case study of the Pucheng County disaster chain on August 10, 2023, in Shaanxi Province, China - Xingang Wang; Sheng Hu; Baoqin Lian; Jiading Wang; Hongbin Zhan; Daozheng Wang; Kai Liu; Li Luo; Chaoying Gu (Engineering Geology, 2024)

Multi-omics revealed molecular mechanism of biphenyl phytoalexin formation in response to yeast extract-induced oxidative stress in Sorbus aucuparia suspension cells - Yuan Li; Jian Yang; Junhui Zhou; Xiufu Wan; Juan Liu; Sheng Wang; Xiaojing Ma; Lanping Guo; Zhiqiang Luo (Plant Cell Reports, 2024)

Corrigendum to “Serviceability evaluation of highway tunnels based on data mining and machine learning: A case study of continental United States” [Tunnelling and Underground Space Technology 142 (2023) 105418] - Ya-Dong Xue; Wei Zhang; Yi-Lin Wang; Wei Luo; Fei Jia; Sheng-Teng Li; Hao-Jun Pang (Tunnelling and Underground Space Technology, 2024)

Long-term MNNG exposure promotes gastric carcinogenesis by activating METTL3/m6A/miR1184 axis-mediated epithelial-mesenchymal transition - Tong Liu; Yan-lu Feng; Rui-ying Wang; Sheng Yang; Yi-ling Ge; Tian-yi Zhang; Jie Li; Cheng-yun Li; Ye Ruan; Bin Luo; Ge-yu Liang (Science of The Total Environment, 2024)

Assessing the effectiveness of 3, 4-dimethylpyrazole phosphate (DMPP) inhibitor in mitigating N2O emissions from contrasting Cd-contaminated soils - Muhammad Laeeq Ur Rehman Hashmi; Yasir Hamid; Muhammad Usman; Jipeng Luo; Sangar Khan; Tang Sheng; Nabila Bano; TalhaTufail Bhatti; Tingqiang Li (Science of The Total Environment, 2024)

Copper overload induces apoptosis and impaired proliferation of T cell in zebrafish - LingYa Li; JiaHao Shi; WenYe Liu; Yi Luo; Sheng Gao; Jing-Xia Liu (Aquatic Toxicology, 2024)

Growth characteristics and biomass model of Cupressus gigantea sapling - Liu Chang-Sheng; Li Tao; Zhang Rui-wen; Wang Chao; Qu Xing-le; Luo Da-qing (Trees, 2024)

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Experimental Investigation on the Motion Characteristics of Air-Floating Tripod Bucket Foundation during Free Floating - Xianqing Liu; Yu Ding; Wenlong Li; Puyang Zhang; Kui Yu; Yutao Feng; Nan Lv; Sheng Luo (Journal of Marine Science and Engineering, 2024)
In recent years, multi-bucket foundations have been studied and gradually adopted in engineering practices as a novel foundation for offshore wind turbines within a range of water depth of 30 to 50 m. This study investigated the motion characteristics of air-floating tripod bucket foundation (AFTBF) through a series of experiments during free air-floating. The experimental results show that the surge force appears to be the most important factor influencing pitch moment and motion, whether it is a change in water depth or a draft for AFTBF. The maximum amplitudes of surge acceleration and pitch angle show a trend of increasing with narrower spacing and decreasing with wider spacing, while the heave acceleration shows an opposite trend. The added mass and damping of heave motion for AFTBF increase with shallower water due to the increasing pressure difference between the inside and bottom of bucket foundation. The shallower the water depth and the larger the draft, the longer the resonance period of heave.

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Cyclophosphamide reduces gene transcriptional activity and embryo in vitro development by inhibiting NF-κB expression through decreasing AcH4K12 - Zhao-Bo Luo; Liu-Hui Yang; Sheng-Zhong Han; Shuang-Yan Chang; Hongye Liu; Zhi-Yong An; Xiu-Li Zhang; Biao-Hu Quan; Xi-Jun Yin; Jin-Dan Kang (Chemico-Biological Interactions, 2024)

The interaction of anti-inflammatory and anti-tumor components in the traditional Chinese medicine Solanum lyratum Thunb - Dian Zou; Xiaohua Li; Xinxin Zhou; Biaobiao Luo; Mohammad Omar Faruque; Sheng Hu; Jian Chen; Xuebo Hu (Natural Product Research, 2023)

Serviceability evaluation of highway tunnels based on data mining and machine learning: A case study of continental United States - Ya-Dong Xue; Wei Zhang; Yi-Lin Wang; Wei Luo; Fei Jia; Sheng-Teng Li; Hao-Jun Pang (Tunnelling and Underground Space Technology, 2023)

Rationally designed calcium carbonate multifunctional trap for contaminants adsorption - Xin Sheng; Shengnan Chen; Zhiwei Zhao; Li Li; Yuanpeng Zou; Hui Shi; Penghui Shao; Liming Yang; Jingsheng Wu; Yaofu Tan; Xinyuan Lai; Xubiao Luo; et al. (Science of The Total Environment, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Characterizing water body changes in Poyang lake using multi-source remote sensing data - Wenyu Wang; Peng Yang; Jun Xia; Shengqing Zhang; Xiangang Luo; Sheng Hu; Jiang Li; Nengcheng Chen; Chesheng Zhan (Environmental Development, 2023)

Defensive furofuran lignans localized to the oil cells of Neocinnamomum delavayi and their metabolism by a specialist insect - Min-Jie Yang; Shi-Hong Luo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

Study on hydrogenation of oxygenated aromatic hydrocarbons via water-gas shift reaction in a subcritical CO-H2O system - Jiale Gu; Huan Li; Wencai Peng; Di Zhu; Jiajia Chen; Shengjie Luo; Siming Liu; Wenxiang Zhao; Youqing Wu; Sheng Huang; Shiyong Wu (Fuel, 2023)

Dose-response formation of N7-(3-benzo[1,3]dioxol-5-yl-2-hydroxypropyl)guanine in liver and urine correlates with micronucleated reticulocyte frequencies in mice administered safrole oxide - Kuen-Yuh Wu; Yu-Tzu Wei; Yu-Syuan Luo; Li-Chin Shen; Bao-Suei Chang; Ya-Yin Chen; Yan-Chi Huang; Hui-Fen Huang; Wen-Sheng Chung; Su-Yin Chiang (Food and Chemical Toxicology, 2023)

The burden of chronic kidney disease associated with dietary exposure to cadmium in China, 2020 - Jiao Huang; Lisha Luo; Yongbo Wang; Siyu Yan; Xuhui Li; Binghui Li; Qiao Huang; Yunyun Wang; Yuanyuan Zhang; Sheng Wei; Yibaina Wang; Xiantao Zeng (Environmental Pollution, 2023)

The Effect of Water Spinach on the Water Quality, Antioxidant System, Non-Specific Immune Response, Growth Performance, and Carbon Balance in Red Tilapia Production - Yuan-Yuan Luo; Xian-Can Chen; Rui-Lin Xie; Zhuo-Hao Ruan; Zhi-Qiang Lu; Liang-Sen Jiang; Yi-Fu Li; Wen-Sheng Liu (Fishes, 2023)
In this study, the compound aquaculture model of red tilapia (O. mossambicus albina × O. urolepis hornorum) and water spinach (Ipomoea aquatica) was used to investigate the effect of water spinach rafts on the water quality, antioxidant system, non-specific immune response, and growth performance of red tilapia and the carbon balance of payments. Red tilapia is characterized by its high adaptability to different production environments and food sources, as one of the most productive fish in aquaculture, and is well accepted in the market due to its nutritional and organoleptic characteristics. The experiment lasted for nine weeks and included two systems: the red tilapia-water spinach raft aquaponics (AP) system with 10% cover ratio with water spinach floating beds, and the aquatic monoculture (AM) system with only red tilapia. The total phosphorus (TP), total nitrogen (TN), and nitrate nitrogen (NO−3-N) in the AM were higher than those in AP from the fifth to ninth week. On the second, third, fifth, and sixth weeks, the ammonia nitrogen (NH4+-N), in the AM was higher than those in the AP. From the seventh week, the pH of the AM was significantly lower than the AP, while the nitrite nitrogen (NO−2-N) was significantly higher than the AP. The water quality index of the AP was better than that of the AM, indicating that water spinach can remove the nutrients from aquaculture water bodies. The average daily gain and specific growth rate (SGR) of fish in AP were higher than those in the AM. The acid phosphatase (ACP), alkaline phosphatase (AKP), and catalase (CAT) activities in the hepatopancreas of red tilapia in the AP were also significantly higher than those in the AM, while the malondialdehyde (MDA) in the AP was lower than the AM. The serum ACP and CAT of red tilapia in the AP were also higher than those in the AM, while the MDA of fish in the AP was lower than the AM. The results showed that both the experimental group and the control group were carbon sources and released greenhouse gases into the atmosphere, but the total carbon emissions of the red tilapia and the water spinach symbiotic system in the experimental group was significantly lower than that of the control group (p

Clerodane diterpenoids from the Uygur medicine Salvia deserta with immunosuppressive activity - Xue Ren; Xin Yuan; Shan-Shan Jiao; Xiao-Ping He; Hong Hu; Juan-Juan Kang; Shi-Hong Luo; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2023)

Effects of Jatrorrhizine on inflammatory response induced by H2O2 in microglia by regulating the MAPK/NF-κB/NLRP3 signaling pathway - Sheng Wang; Cai-Li Xu; Tao Luo; Hua-Qiao Wang (Molecular Neurobiology, 2023)

A new maintenance mechanism of species diversities on tussocks under water level change - Xue Wang; Yue Li; Lianxi Sheng; Liang Ma; Hong Yan; Wenbo Luo (Hydrobiologia, 2023)

Correction to: Relationship between the characterization of natural colloids and metal elements in surface waters - Caixia Yan; Yanru Sheng; Min Ju; Cong Ding; Qian Li; Ziwei Luo; Mingjun Ding; Minghua Nie (Environmental Science and Pollution Research, 2023)

Neurobehavioral disorders induced by environmental zinc in female zebrafish (Danio rerio): Insights from brain and intestine transcriptional and metabolic signatures - Fan Yu; Zhi-Shuai Hou; Hong-Rui Luo; Hong-Xia Li; Xue-Fan Cui; Jian-Lin Li; Wen-Rong Feng; Yong-Kai Tang; Sheng-Yan Su; Qin-Feng Gao; Jun Xiao; Pao Xu (Chemosphere, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Elevated O2 alleviated anaerobic metabolism in postharvest winter jujube fruit by regulating pyruvic acid and energy metabolism - Dong Li; Li Li; Wenxuan Li; Yanqun Xu; Xueyuan Han; Nina Bao; Zhanwu Sheng; Yaya Yuan; Xingtao Zhang; Zisheng Luo (Postharvest Biology and Technology, 2023)

A harsh environment resistant robust Co(OH)2@stearic acid nanocellulose-based membrane for oil-water separation and wastewater purification - Zuozhu Yin; Min Li; Zihao Li; Yuanting Deng; Mingshan Xue; Yuhua Chen; Junfei Ou; Sheng Lei; Yidan Luo; Chan Xie (Journal of Environmental Management, 2023)

Development and characterization of walnut oleogels structured by cellulose nanofiber - Xiufen Li; Guanshui Guo; Yuxuan Zou; Jia Luo; Jun Sheng; Yang Tian; Jienan Li (Food Hydrocolloids, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Spatial–Temporal Evolution and Countermeasures for Coal and Gas Outbursts Represented as a Dynamic System - Chaojun Fan; Lingjin Xu; Derek Elsworth; Mingkun Luo; Ting Liu; Sheng Li; Lijun Zhou; Weiwei Su (Rock Mechanics and Rock Engineering, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

A new strategy to study geochemical characteristics and migration of crude oils in Zhu I Depression, Pearl River Mouth Basin, South China Sea - Xuanbo Gao; Siyuan Di; Xianfeng Tan; Wanfeng Zhang; Jia Wang; Long Luo; Xuejiao Qu; Jianping Liu; Shengyu Li; Nan Jiang; Sheng He; Shukui Zhu (Organic Geochemistry, 2023)

A new sesquiterpene synthase catalyzing the formation of (R)-β-bisabolene from medicinal plant Colquhounia coccinea var. mollis and its anti-adipogenic and antibacterial activities - De-Sen Li; Lin-Lin Shi; Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Yue-Gui Chen; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

Valorization of thermally hydrolyzed sludge with clay for sintering of ceramic tiles - Lei Wen; Lin Lin; Yi-ang Fan; Yang Luo; Sheng-shou Ma; Ying Zhou; Chao Yang; Kaimin Shih; Xiao-yan Li (Science of The Total Environment, 2023)

Cytoplasmic Hsp70s promote EcR transport into the nucleus by responding to various stimuli - Jun Gu; Yan Ye; Zi-Wen Zheng; Wei Luo; Yan-Jun Gong; Qi-Li Feng; Sheng Li; Li-Hua Huang (Insect Biochemistry and Molecular Biology, 2023)

All-ceramic array patch for 5G signal enhancement based on B-site substituted zinc-cobalt molybdate low temperature co-fired ceramics - Fuyu Li; Yuanxun Li; Sheng Li; Yang Luo; Yongcheng Lu; Tingting Tang; Yulong Liao; Jinping Zhang; Qiye Wen (Chemical Engineering Journal, 2023)

RNAi-mediated knockdown of the mandibular organ-inhibiting hormone (MOIH) gene stimulates vitellogenesis in the Chinese mitten crab Eriocheir sinensis - Shuquan Ding; Mengting Huang; Na Sheng; Tiantian Chen; Ruihan Xu; Zhaoyuan Luo; Xiuqin Huang; Zhicheng Wan; Shiping Su; Xilei Li (Fisheries Science, 2023)

Spatio-temporal heterogeneity in the international trade resilience during COVID-19 - Wei Luo; Lingfeng He; Zihui Yang; Shirui Zhang; Yong Wang; Dianbo Liu; Sheng Hu; Li He; Jizhe Xia; Min Chen (Applied Geography, 2023)

Three Days Delayed Recanalization Improved Neurological Function in pMCAO Rats by Increasing M2 Microglia—Possible Involvement of the IL-4R/STAT6/PPARγ Pathway - Ruiqing Kang; Marcin Gamdzyk; Yujie Luo; Hong Tang; Lei Huang; Cameron Lenahan; Desislava Doycheva; Dujuan Li; Jiping Tang; Sheng Tan; John H. Zhang (Translational Stroke Research, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Preparation of Al-Si alloy from silicon cutting waste: Enabling oxide surface removing and silicon utilization improving via vacuum sintering - Guangyu Chen; Yan Li; Liuqing Huang; Yuanhao Yang; Wang Sheng; Chentong Zhang; Xuetao Luo (Science of The Total Environment, 2023)

Direct electrochemical detection of Cu(Ⅱ) ions in juice and tea beverage samples using MWCNTs-BMIMPF6-Nafion modified GCE electrodes - Gangfeng Li; Shaobiao Feng; Lili Yan; Lijuan Yang; Bei Huo; Liuliu Wang; Sheng Luo; Dexin Yang (Food Chemistry, 2023)

DGT method for the in situ measurement of triazines and the desorption kinetics of atrazine in soil - Siheng Zheng; Feng Sheng; Cheng Gu; Yanying Li; Zhou Fang; Jun Luo (Environmental Science and Pollution Research, 2023)

Long-term cadmium exposure impairs cognitive function by activating lnc-Gm10532/m6A/FIS1 axis-mediated mitochondrial fission and dysfunction - Ping Deng; Huadong Zhang; Liting Wang; Sheng Jie; Qi Zhao; Fengqiong Chen; Yang Yue; Hui Wang; Li Tian; Jia Xie; Mengyan Chen; Yan Luo; et al. (Science of The Total Environment, 2023)

Labdane diterpenoids from the heartwood of Leucosceptrum canum that impact on root growth and seed germination of Arabidopsis thaliana - Yan Liu; Yan-Ying Zhou; Shi-Hong Luo; Kai Guo; Man-Wen Zhang; Shu-Xi Jing; Chun-Huan Li; Juan Hua; Sheng-Hong Li (Phytochemistry, 2023)

Transcriptome analysis and functional gene identification reveals potential mechanisms of heat stress response of Lactiplantibacillus plantarum CGMCC8198 - Jia-Yi Da; Mao-Sheng Xi; Han-Lu Li; Min-Min Liu; Cheng-Hui Zhou; Zhong-Yuan Li; Ya-Jian Song; Sa Zhou; Tong-Cun Zhang; Xue-Gang Luo (Food Bioscience, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Remote sensing inversion and prediction of land use land cover in the middle reaches of the Yangtze River basin, China - Shengqing Zhang; Peng Yang; Jun Xia; Wenyu Wang; Wei Cai; Nengcheng Chen; Sheng Hu; Xiangang Luo; Jiang Li; Chesheng Zhan (Environmental Science and Pollution Research, 2023)

Mixed heavy metals exposure affects the renal function mediated by 8-OHG: A cross-sectional study in rural residents of China - Xiaoyu Tian; Xiaobing Shan; Li Ma; Chenyang Zhang; Mei Wang; Jie Zheng; Ruoyi Lei; Li He; Jun Yan; Xun Li; Yanjun Bai; Keqin Hu; et al. (Environmental Pollution, 2023)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Transcriptome analysis and co‐expression network reveal the mechanism linking mitochondrial function to immune regulation in red crucian carp ( Carassius auratus red var) after Aeromonas hydrophila challenge - Ning‐Xia Xiong; Xu‐Ying Kuang; Zi‐Xuan Fang; Jie Ou; Shi‐Yun Li; Jia‐Hui Zhao; Jin‐Fang Huang; Ke‐Xin Li; Rou Wang; Lan‐Fen Fan; Sheng‐Wei Luo; Shao‐Jun Liu (Journal of Fish Diseases, 2022)
Aeromonas hydrophila is a common pathogen of freshwater fish. In this study, A. hydrophila infection was shown to cause tissue damage, trigger physiological changes as well as alter the expression profiles of immune‐ and metabolic‐related genes in immune tissues of red crucian carp (RCC). Transcriptome analysis revealed that acute A. hydrophila infection exerted a profound effect on mitochondrial oxidative phosphorylation linking metabolic regulation to immune response. In addition, we further identified cellular senescence, apoptosis, necrosis and mitogen‐activated protein kinase signal pathways as crucial signal pathways in the kidney of RCC subjected to A. hydrophila infection. These findings may have important implications for understanding modulation of immunometabolic response to bacterial infection.

Novel SNPs in the 3′UTR Region of GHRb Gene Associated with Growth Traits in Striped Catfish (Pangasianodon hypophthalmus), a Valuable Aquaculture Species - Liang-Sen Jiang; Zhuo-Hao Ruan; Zhi-Qiang Lu; Yi-Fu Li; Yuan-Yuan Luo; Xi-Quan Zhang; Wen-Sheng Liu (Fishes, 2022)
The striped catfish, Pangasianodon hypophthalmus is an important freshwater aquaculture species in Southeast Asian countries due to its rapid growth. The growth hormone receptor (GHR) is a significant regulatory factor for the growth axis and has great potential applications in animal genetic breeding. This study aims to characterize the GHRb cDNA of the striped catfish and analyze the distribution of its mRNA. Screening of single nucleotide polymorphisms’ (SNPs) loci and diplotypes was performed to provide basic information for the assisted selection of molecular markers in genetic breeding. The results showed that the GHRb cDNA of striped catfish had 2791 bp, which encoded for 569 amino acids. In a phylogenyic study, the ghrb of the striped catfish was clustered with those of other catfish and they were highly homologous. Quantitative real-time PCR (qRT-PCR) experiments showed that GHRb mRNA was expressed in ten different organs of the striped catfish, with the highest expression level in the liver. Five SNP and a haplotype block were identified in the 3′UTR of the GHRb gene using the direct sequencing of 307 individuals. Three haplotypes were found and four diplotypes were constructed. The association analysis revealed that these polymorphisms were significantly associated with growth traits in the striped catfish (p

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

De Novo SMARCC2 Variant in a Chinese Woman with Coffin-Siris Syndrome 8: a Case Report with Mild Intellectual Disability and Endocrinopathy - Sheng Yi; Mengting Li; Qi Yang; Zailong Qin; Shang Yi; Juanjuan Xu; Junjie Chen; Hao Wei; Yaoyao Jiang; Rongmin Wei; Qinle Zhang; Chengyun Yang; et al. (Journal of Molecular Neuroscience, 2022)

Analytical solution of external water pressure on deep tunnel lining in horizontally layered hydrogeological structures - Sheng Luo; Mo Xu; Xiaobing Kang; Xiaoxue Li; Lifang Rao (Bulletin of Engineering Geology and the Environment, 2022)

Ambient temperature, humidity, and urinary system diseases: a population-based study in Western China - Yanlin Li; Bo Wang; Shunxia Wang; Shenggang Xu; Sheng Li; Hupeng He; Jingping Niu; Bin Luo (Environmental Science and Pollution Research, 2022)

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

Correction to: Enhanced adsorption of phosphorus in soil by lanthanum-modified biochar: improving phosphorus retention and storage capacity - Di Zhao; Yuan Luo; Yi-yang Feng; Qiu-ping He; Li-sheng Zhang; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2021)

Enhanced adsorption of phosphorus in soil by lanthanum-modified biochar: improving phosphorus retention and storage capacity - Di Zhao; Yuan Luo; Yi-yang Feng; Qiu-ping He; Li-sheng Zhang; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2021)

Comparative genomic analysis of Mycoplasma anatis strains - Qi Zhou; Kaijie Mai; Dehong Yang; Junfa Liu; Zhuanqiang Yan; Cuifen Luo; Yangtong Tan; Sheng Cao; Qingfeng Zhou; Li Chen; Feng Chen (Genes & Genomics, 2021)

Two new isoquinoline alkaloids from the seeds of Nandina domestica - Juan Qin; Sheng-Yuan Zhang; Yu-Bo Zhang; Li-Feng Chen; Neng-Hua Chen; Zhong-Nan Wu; Ding Luo; Guo-Cai Wang; Yao-Lan Li (Natural Product Research, 2021)

Design and Evaluation of Multiplex One-Step Reverse Transcription PCR–Dipstick Chromatography Method for the Analysis of Seven Respiratory Pathogens - Li Luo; Qianming Chen; Sheng Qin; Qiang Luo; Zhenjie Liu; Qiong Li; Shuilan Zheng; Xianzhang Huang; Peifeng Ke; Xiangsheng Yang; Hui Xiao; Ning Xu (Current Microbiology, 2021)

Association of myostatin deficiency with collagen related disease-umbilical hernia and tippy toe standing in pigs - Hyo-Jin Paek; Zhao-Bo Luo; Hak-Myong Choe; Biao-Hu Quan; Kai Gao; Sheng-Zhong Han; Zhou-Yan Li; Jin-Dan Kang; Xi-Jun Yin (Transgenic Research, 2021)

Cyclin-dependent kinase inhibitor 1B acts as a novel molecule to mediate testosterone synthesis and secretion in mouse Leydig cells by luteinizing hormone (LH) signaling pathway - Hongzhou Guo; Xuan Luo; Longjie Sun; Jianhua Li; Sheng Cui (In Vitro Cellular & Developmental Biology - Animal, 2021)

A multi-domain prognostic model of disorder of consciousness using resting-state fMRI and laboratory parameters - Yamei Yu; Fanxia Meng; Li Zhang; Xiaoyan Liu; Yuehao Wu; Sicong Chen; Xufei Tan; Xiaoxia Li; Sheng Kuang; Yu Sun; Benyan Luo (Brain Imaging and Behavior, 2021)

Astragaloside IV inhibits adriamycin-induced cardiac ferroptosis by enhancing Nrf2 signaling - Li-Fei Luo; Peng Guan; Lu-Yun Qin; Jian-Xin Wang; Na Wang; En-Sheng Ji (Molecular and Cellular Biochemistry, 2021)

The association between drought and outpatient visits for respiratory diseases in four northwest cities of China - Bo Wang; Shunxia Wang; Lanyu Li; Shenggang Xu; Chengyun Li; Sheng Li; Jinyu Wang; Hupeng He; Jingping Niu; Kai Zhang; Bin Luo (Climatic Change, 2021)

Brucellosis screening and follow-up of seropositive asymptomatic subjects among household members of shepherds in China - Jing Hu; Xiangyi Zhang; Huixin Yang; Siwen Zhang; Taijun Wang; Shuqi An; Mujinyan Li; Fande Li; Jingjing Luo; Fangfang Hu; Dali Wang; Shaonan Ni; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

An efficient parallel computing strategy for the processing of large GNSS network datasets - Yang Cui; Zhengsheng Chen; Linyang Li; Qinghua Zhang; Sheng Luo; Zhiping Lu (GPS Solutions, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Noroleanane-type triterpenoids from Dolichos trilobus L. and their anti-α-glucosidase activities - Ming Luo; Yan-Hong Li; Ya Lu; Yan Yuan; Rong-Sheng Ruan; Yong-Ming Chuan; Kai Tian; Xiang-Zhong Huang (Natural Product Research, 2021)

Ferroptosis occurs in phase of reperfusion but not ischemia in rat heart following ischemia or ischemia/reperfusion - Li-Jing Tang; Xiu-Ju Luo; Hua Tu; Heng Chen; Xiao-Ming Xiong; Nian-Sheng Li; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Mapping the permafrost stability on the Tibetan Plateau for 2005–2015 - Youhua Ran; Xin Li; Guodong Cheng; Zhuotong Nan; Jinxing Che; Yu Sheng; Qingbai Wu; Huijun Jin; Dongliang Luo; Zhiguang Tang; Xiaobo Wu (Science China Earth Sciences, 2021)

Spinal CCL2 Promotes Pain Sensitization by Rapid Enhancement of NMDA-Induced Currents Through the ERK-GluN2B Pathway in Mouse Lamina II Neurons - Hui Zhang; Sui-Bin Ma; Yong-Jing Gao; Jun-Ling Xing; Hang Xian; Zhen-Zhen Li; Shu-Ning Shen; Sheng-Xi Wu; Ceng Luo; Rou-Gang Xie (Neuroscience Bulletin, 2020)
Previous studies have shown that CCL2 (C–C motif chemokine ligand 2) induces chronic pain, but the exact mechanisms are still unknown. Here, we established models to explore the potential mechanisms. Behavioral experiments revealed that an antagonist of extracellular signal-regulated kinase (ERK) inhibited not only CCL2-induced inflammatory pain, but also pain responses induced by complete Freund’s adjuvant. We posed the question of the intracellular signaling cascade involved. Subsequent experiments showed that CCL2 up-regulated the expression of phosphorylated ERK (pERK) and N-methyl D-aspartate receptor [NMDAR] subtype 2B (GluN2B); meanwhile, antagonists of CCR2 and ERK effectively reversed these phenomena. Whole-cell patch-clamp recordings revealed that CCL2 enhanced the NMDAR-induced currents via activating the pERK pathway, which was blocked by antagonists of GluN2B and ERK. In summary, we demonstrate that CCL2 directly interacts with CCR2 to enhance NMDAR-induced currents, eventually leading to inflammatory pain mainly through the CCL2–CCR2–pERK–GluN2B pathway.

Chronic minocycline treatment exerts antidepressant effect, inhibits neuroinflammation, and modulates gut microbiota in mice - Qi Yang; Li Luo; Ting Sun; Le Yang; Li-Fei Cheng; Yan Wang; Qing-Qing Liu; An Liu; Hai-Yan Liu; Ming-Gao Zhao; Sheng-Xi Wu; Bin Feng (Psychopharmacology, 2020)

Ginsenosides in root exudates of Panax notoginseng drive the change of soil microbiota through carbon source different utilization - Li-Fen Luo; Lei Yang; Zheng-Xu Yan; Bing-Bing Jiang; Su Li; Hui-Chuan Huang; Yi-Xiang Liu; Shu-Sheng Zhu; Min Yang (Plant and Soil, 2020)

Identification of Cyt2Ba from a New Strain of Bacillus thuringiensis and Its Toxicity in Bradysia difformis - Fan-Fan Wang; Shao-Xuan Qu; Jin-Sheng Lin; Hui-Ping Li; Li-Juan Hou; Ning Jiang; Xin Luo; Lin Ma (Current Microbiology, 2020)
Bradysia difformis is one of the most damaging pests in mushroom production in China. In this study, eight Bacillus thuringiensis strains were analyzed for insecticidal activity in B. difformis . The strain JW-1 showed the highest insecticidal activity against B. difformis larvae, but did not inhibit the mycelial growth of Pleurotus ostreatus and P. geesteranus . The 16S rRNA gene (1397 bp) and cyt2 gene (792 bp) were obtained from strain JW-1. The phylogenetic tree based on 16S rRNA gene and Cyt2 toxin showed that strain JW-1 was a member of B. thuringiensis and Cyt2 toxin belonged to Cyt2Ba toxin cluster. The Cyt2Ba toxin from strain JW-1 was overexpressed in E. coli as a fusion protein and the fusion protein (70 kDa) was purified by Ni-IDA affinity chromatography. The purified Cyt2Ba fusion protein was toxic to B. difformis larvae (LC 50 was 2.25 ng/mL). The identification of Cyt2Ba from strain JW-1 and confirmation of the insecticidal activity of Cyt2Ba in B. difformis provided a new means of biological control of the important pest in mushroom production.

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Relationship between the characterization of natural colloids and metal elements in surface waters - Caixia Yan; Yanru Sheng; Min Ju; Cong Ding; Qian Li; Ziwei Luo; Mingjun Ding; Minghua Nie (Environmental Science and Pollution Research, 2020)

Directional seismic response to the complex topography: A case study of 2013 Lushan Ms 7.0 earthquake - Bo Zhao; Yun-sheng Wang; Li-jun Su; Yong-hong Luo; Jing Zhang (Journal of Mountain Science, 2020)

Effect of Calcium-Based Catalysts on Pyrolysis Liquid Products from Municipal Sludge - Wei Luo; Yi-Feng Su; Qing Hu; Huai-Lin Yin; Shuo Wang; Li-Jiao Ao; Xiao-Xi Wen; Sheng-Xiong Huang; Nan Zhou; Wei Zhang; Zhi Zhou (BioEnergy Research, 2020)

Reducing the Common Environmental Effect on Litopenaeus vannamei Body Weight by Rearing Communally at Early Developmental Stages and Using a Reconstructed Pedigree - Zhangwei Kong; Jie Kong; Dongchun Hao; Xia Lu; Tan Jian; Xianhong Meng; Kun Luo; Baoxiang Cao; Juan Sui; Xupeng Li; Sheng Luan (Journal of Ocean University of China, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

Prevalence of RNF213 variants in symptomatic intracranial arterial stenosis/occlusion in China - Xunsha Sun; Man Luo; Jiaoxing Li; Rong Lai; Jing Lin; Yufang Wang; Xiaowei Xu; Shaoqing Wu; Wenli Sheng (Molecular Genetics and Genomics, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Anfibatide Preserves Blood–Brain Barrier Integrity by Inhibiting TLR4/RhoA/ROCK Pathway After Cerebral Ischemia/Reperfusion Injury in Rat - Peng Gong; Rui Li; Hui-Yu Jia; Zheng Ma; Xiao-Yi Li; Xiang-rong Dai; Sheng-Yong Luo (Journal of Molecular Neuroscience, 2020)

Perception of and Behavioral Responses to Host Plant Volatiles for Three Adelphocoris Species - Chun-Li Xiu; Hong-Sheng Pan; Bing Liu; Zong-Xiu Luo; Livy Williams; Yi-Zhong Yang; Yan-Hui Lu (Journal of Chemical Ecology, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Main Mechanism for Generating Overpressure in the Paleogene Source Rock Series of the Chezhen Depression, Bohai Bay Basin, China - Junli Zhang; Sheng He; Yuqin Wang; Yongshi Wang; Xuefeng Hao; Shengyuan Luo; Ping Li; Xuewei Dang; Ruizhi Yang (Journal of Earth Science, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

Immunomodulatory effect of mesenchymal stem cells: Cell origin and cell quality variations - Marwa El-Sayed; Mohamed Ali El-Feky; Mostafa I. El-Amir; Al Shaimaa Hasan; Mohammed Tag-Adeen; Yoshishige Urata; Shinji Goto; Lan Luo; Chen Yan; Tao-Sheng Li (Molecular Biology Reports, 2019)

A new actinomycin Z analogue with an additional oxygen bridge between chromophore and β -depsipentapeptide from Streptomyces sp. KIB-H714 - Miao Dong; Pei Cao; Ya-Tuan Ma; Jianying Luo; Yijun Yan; Rong-Tao Li; Sheng-Xiong Huang (Natural Product Research, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Combination of Emricasan with Ponatinib Synergistically Reduces Ischemia/Reperfusion Injury in Rat Brain Through Simultaneous Prevention of Apoptosis and Necroptosis - Jing Tian; Shu Guo; Heng Chen; Jing-Jie Peng; Miao-Miao Jia; Nian-Sheng Li; Xiao-Jie Zhang; Jie Yang; Xiu-Ju Luo; Jun Peng (Translational Stroke Research, 2018)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Influence of white spot syndrome virus infection on hepatopancreas gene expression of ‘Huanghai No. 2’ shrimp (Fenneropenaeus chinensis) - Xianhong Meng; Xiaoli Shi; Jie Kong; Sheng Luan; Kun Luo; Baoxiang Cao; Ning Liu; Xia Lu; Xupeng Li; Kangyu Deng; Jiawang Cao; Yingxue Zhang; et al. (Journal of Ocean University of China, 2017)

Developing a risk assessment system for gas tunnel disasters in China - Xiao-bing Kang; Sheng Luo; Qing-shan Li; Mo Xu; Qiang Li (Journal of Mountain Science, 2017)

Molecular and immune response characterizations of a novel Bax inhibitor-1 gene in pufferfish, Takifugu obscurus - Chang-Hong Cheng; Sheng-Wei Luo; An-Li Wang; Zhi-Xun Guo (Fish Physiology and Biochemistry, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

Phthalates in plastic bottled non-alcoholic beverages from China and estimated dietary exposure in adults - Ji-Feng Yang; Li-Ming Yang; Li-Ying Zheng; Guang-Guo Ying; Cheng-Bin Liu; Sheng-Lian Luo (Food Additives & Contaminants Part B-Surveillance, 2017)

Molecular detection and genome characterization of porcine circovirus type 2 in rats captured on commercial swine farms - Shao-Lun Zhai; Sheng-Nan Chen; Wei Liu; Xiao-Peng Li; Su-Fang Deng; Xiao-Hui Wen; Man-Lin Luo; Dian-Hong Lv; Wen-Kang Wei; Rui-Ai Chen (Archives of Virology, 2016)

A polydnaviral genome of Microplitis bicoloratus bracovirus and molecular interactions between the host and virus involved in NF-κB signaling - Dong-Shuai Yu; Ya-Bin Chen; Ming Li; Ming-Jun Yang; Yang Yang; Jian-Sheng Hu; Kai-Jun Luo (Archives of Virology, 2016)

Genetic and phylogenetic analysis of a novel parvovirus isolated from chickens in Guangxi, China - Bin Feng; Zhixun Xie; Xianwen Deng; Liji Xie; Zhiqin Xie; Li Huang; Qin Fan; Sisi Luo; Jiaoling Huang; Yanfang Zhang; Tingting Zeng; Sheng Wang; et al. (Archives of Virology, 2016)

Inhibition of the oxidative stress-induced miR-23a protects the human retinal pigment epithelium (RPE) cells from apoptosis through the upregulation of glutaminase and glutamine uptake - Dan-dan Li; Bin-wu Zhong; Hai-xia Zhang; Hong-yan Zhou; Jie Luo; Yang Liu; Gui-chun Xu; Chun-sheng Luan; Jun Fang (Molecular Biology Reports, 2016)

Avian reovirus σA and σNS proteins activate the phosphatidylinositol 3-kinase-dependent Akt signalling pathway - Liji Xie; Zhixun Xie; Li Huang; Qing Fan; Sisi Luo; Jiaoling Huang; Xianwen Deng; Zhiqin Xie; Tingting Zeng; Yanfang Zhang; Sheng Wang (Archives of Virology, 2016)

Genetic parameters for cold tolerance and body weight of Chinese fleshy prawn, Fenneropenaeus chinensis - Wenjia Li; Sheng Luan; Kun Luo; Juan Sui; Xia Lu; Qingyin Wang; Jie Kong (Acta Oceanologica Sinica, 2016)

Three-dimensional water quality model based on FVCOM for total load control management in Guan River Estuary, Northern Jiangsu Province - Li Zhang; Weibo Lin; Keqiang Li; Jianming Sheng; Aihong Wei; Feng Luo; Yan Wang; Xiulin Wang; Longjun Zhang (Journal of Ocean University of China, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Transgenic NfFeSOD Sedum alfredii plants exhibited profound growth impairments and better relative tolerance to long-term abiotic stresses - Xiang Gao; Wen-Li Ai; Huan Gong; Li-Juan Cui; Bo-Xia Chen; Hong-Yi Luo; Zhong-Chun Zhang; Bao-Sheng Qiu (Plant Biotechnology Reports, 2016)

The substrate promiscuity of a phosphopantetheinyl transferase SchPPT for coenzyme A derivatives and acyl carrier proteins - Yue-Yue Wang; Hong-Dou Luo; Xiao-Sheng Zhang; Tao Lin; Hui Jiang; Yong-Quan Li (Archives of Microbiology, 2016)

Comparison of clinical outcomes of patients with non-small-cell lung cancer harbouring epidermal growth factor receptor exon 19 or exon 21 mutations after tyrosine kinase inhibitors treatment: a meta-analysis - Miaomiao Sheng; Fang Wang; Yueguang Zhao; Shanshan Li; Xiaojie Wang; Tao Shou; Ying Luo; Wenru Tang (European Journal of Clinical Pharmacology, 2016)

The impact of nitrogen amendment and crop growth on dissolved organic carbon in soil solution - Xiao-guo Wang; Chang-sheng Li; Yong Luo; Ke-ke Hua; Ming-hua Zhou (Journal of Mountain Science, 2016)

Genome characterization and phylogenetic analysis of a lineage IV peste des petits ruminants virus in southern China - Xiao-Peng Li; Shao-Lun Zhai; Dong-Sheng He; Peng-Ju Guo; Dian-Hong Lv; Xiao-Hui Wen; Man-Lin Luo; Rui-Ai Chen; Wen-Kang Wei (Virus Genes, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

A Randomized and Controlled Multicenter Prospective Study of the Chinese Medicinal Compound Fufang Xuelian Burn Ointment for the Treatment of Superficial and Deep Second-Degree Burn Wounds - Jing Ouyang; Yong-chuan Chen; Gao-xing Luo; Hong Yan; Yi-zhi Peng; Yue-sheng Huang; Pei-yuan Xia; Qin Zhang; Zhen-jiang Liao; Guo-hui Li; Xiao-dong Yang; Yong-qing Cai (Cell Biochemistry and Biophysics, 2014)

Silencing heat shock protein 27 (HSP27) inhibits the proliferation and migration of vascular smooth muscle cells in vitro - Jie Huang; Liang-di Xie; Li Luo; Su-li Zheng; Hua-jun Wang; Chang-sheng Xu (Molecular and Cellular Biochemistry, 2014)

The activation of TLR7 regulates the expression of VEGF, TIMP1, MMP2, IL-6, and IL-15 in Hela cells - Lei Li; Feng-Wei Cheng; Fang Wang; Bo Jia; Xin Luo; Sheng-Quan Zhang (Molecular and Cellular Biochemistry, 2014)

Left hemiparalexia of Chinese characters: neglect dyslexia or disruption of pathway of visual word form processing? - Wenchao Yi; Ting Wu; Wei Chen; Ti-fei Yuan; Benyan Luo; Chunlei Shan; Jianan Li; Sheng He; Xuchu Weng (Brain Structure and Function, 2014)

Involvement of JNK in the Embryonic Development and Organogenesis in Zebrafish - Yamei Xiao; Yonghua Zhou; Zhen Xiong; Lijun Zou; Minggui Jiang; Zhongwen Luo; Sheng Wen; Wenbin Liu; Shaojun Liu; Wancheng Li (Marine Biotechnology, 2013)

Effects of four antitussives on airway neurogenic inflammation in a guinea pig model of chronic cough induced by cigarette smoke exposure - Yu-long Luo; Pei-bo Li; Chen-chen Zhang; Yan-fang Zheng; Sheng Wang; Yi-chu Nie; Ke-jian Zhang; Wei-wei Su (Inflammation Research, 2013)

Gardiquimod inhibits the expression of calcium-induced differentiation markers in HaCaT cells - Bo Jia; Xin Luo; Feng-Wei Cheng; Lei Li; Dao-Jun Hu; Fang Wang; Sheng-Quan Zhang (Molecular Biology Reports, 2013)

Correlation of Nr4a2 Expression with the Neuron Progenitors in Adult Zebrafish Brain - Sheng Chen; Guang Rui Luo; Ting Li; Ting Xi Liu; Weidong Le (Journal of Molecular Neuroscience, 2013)

Synthesis and in vitro cytotoxic evaluation of novel $$N$$ -(3,4,5-trimethoxyphenyl)pyridin-2( $$1H$$ )-one derivatives - Taijie Chen; Yu Luo; Li Sheng; Jia Li; Youhong Hu; Wei Lu (Molecular Diversity, 2013)

Revealing storage-area relationship of open water in ungauged subalpine wetland — Napahai in Northwest Yunnan, China - Jie Li; Jin-ming Hu; Wei Deng; Sheng-li Huang; Hai-feng Jia; Chun-ling Zhu; Huai-xiu Luo (Journal of Mountain Science, 2013)
Mountains and plateaus in Southwest China contain many subalpine and alpine wetlands, with significant hydroecological functions. But ungauged or poorly gauged conditions limit the study and understanding of hydrological regimes of these wetland types. This study selects an ungauged subalpine wetland — Napahai in Northwest Yunnan, China — as a case for developing a practical approach to revealing its storage-area relationship of open water. A Trimble R8 GNSS (Global Navigation Satellites Systems) RTK (Real-time Kinematic system) and sonar fathometer were used to survey fine-resolution elevation data and generate a digital elevation model of the Napahai Wetland. Forty-four Landsat images from 1987 to 2011 were collected, and the Normalized Difference Water Index was used to classify open water features in the area. The area of open water in Napahai was calculated for each phase. With these data and a developed conceptual model, the storage of open water for each phase was estimated using ArcGIS tools. Both storage and area of open water showed significant intra-annual and inter-annual variations. In the rainy season, the monthly change of average storage of open water in Napahai showed about 1–2 months lag behind mean monthly rainfall. The storage-area relationship of open water was well fit by a power function equation ( R 2 ≈0.91, n =44). This study indicates that if detailed elevations are available for similarly ungauged subalpine wetlands in Southwest China, researchers can use this practical approach to estimate multi-temporal areas and storages and reveal the storage-area relationship of open water in the wetlands. The study provided valuable information of this case wetland for optimizing its hydro-ecological managements and a new method to wetland researchers and managers for the hydrological study of similarly ungauged wetland complex.

Hydro-mechanical coupling experiments on suffusion in sandy gravel foundations containing a partially penetrating cut-off wall - Yu-long Luo; Qiang Wu; Mei-li Zhan; Jin-chang Sheng; Yuan Wang (Natural Hazards, 2013)

Genome-wide analysis of aberrantly expressed circulating miRNAs in patients with coal workers’ pneumoconiosis - Li Guo; Xiaoming Ji; Sheng Yang; Zhiguo Hou; Chen Luo; Jingjing Fan; Chunhui Ni; Feng Chen (Molecular Biology Reports, 2013)

Hydro-mechanical experiments on suffusion under long-term large hydraulic heads - Yu-long Luo; Liang Qiao; Xing-xing Liu; Mei-li Zhan; Jin-chang Sheng (Natural Hazards, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Polymorphisms in luteinizing hormone receptor and hypothalamic gonadotropin-releasing hormone genes and their effects on sperm quality traits in Chinese Holstein bulls - Li-Ping Sun; Qing-Zhi Du; Ya-Pan Song; Jun-Na Yu; Shu-Juan Wang; Lei Sang; Luo-Wen Song; Yao-Min Yue; Yu-Ze Lian; Sheng-Li Zhang; Guo-Hua Hua; Shu-Jun Zhang; et al. (Molecular Biology Reports, 2012)

Cell-specific distributions of estrogen receptor alpha (ERα) and androgen receptor (AR) in anterior pituitary glands from adult cockerels as revealed by immunohistochemistry - Dehao Sun; Tongtong Cui; Haoshu Luo; Ruiguo Li; Sheng Cui; Jiali Liu (Cell and Tissue Research, 2012)

Targeted killing effects of double CD and TK suicide genes controlled by survivin promoter on gastric cancer cell - Xian-Run Luo; Jian-Sheng Li; Ying Niu; Li Miao (Molecular Biology Reports, 2011)

Characterization of a Rolling-Circle Replication Plasmid pLR1 from Lactobacillus plantarum LR1 - Ruoyu Li; Zhengyuan Zhai; Sheng Yin; Ying Huang; Qing Wang; Yunbo Luo; Yanling Hao (Current Microbiology, 2009)

Cold storage and cryopreservation of hairy root cultures of medicinal plant Eruca sativa Mill., Astragalus membranaceus and Gentiana macrophylla Pall. - Sheng-Hui Xue; Xin-Juan Luo; Zhen-Hua Wu; Hui-Li Zhang; Xin-Yu Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2008)

Overexpression of AeNHX1, a root-specific vacuolar Na+/H+ antiporter from Agropyron elongatum, confers salt tolerance to Arabidopsis and Festuca plants - Wei Hua Qiao; Xiang Yu Zhao; Wei Li; Yan Luo; Xian Sheng Zhang (Plant Cell Reports, 2007)

A new dihydroisocoumarin from the rhizomes of Notopterygium forbesii - Yan-Hui Li; Fan Luo; Shu-Lin Peng; Jian Liang; Li-Sheng Ding (Natural Product Research, 2006)

Construction of a genetic linkage map and QTL analysis of fiber-related traits in upland cotton (Gossypium hirsutum L.) - Zheng-Sheng Zhang; Yue-Hua Xiao; Ming Luo; Xian-Bi Li; Xiao-Ying Luo; Lei Hou; De-Mou Li; Yan Pei (Euphytica, 2005)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

Sedimentary cycles of trace elements in Salawusu River Valley since 150 ka BP - Yao Chun-xial; Li Bao-sheng; Jin He-ling; David Dian Zhang; Yan Man-cun; Zhu Yi-zhi; Li Hou-xin; Zhang Yu-hong; Luo Kai-li (Journal of Geographical Sciences, 2002)

CaCO3 cycles in salawusu river basin since 150ka B.P. - Kai-li Luo; Bao-sheng Li; Yi-zhi Zhu; He-ling Jin; David Dian Zhang; Man-cun Yan; Hou-xin Li; Chun-xia Yao; Yu-hong Zhang (Chinese Geographical Science, 2001)